(untitled) (Mustansiria Dental Journal, 2018)
To evaluate the effects of first premolar extraction on third molar angulation during fixed orthodontic treatment. Panoramic radiographs of 40 patients treated orthodontically by fixed appliances were evaluated for change in third molar angulation. Twenty patients were treated by extraction of first premolars, whereas the other 20 patients were treated nonextraction. The change in upper and lower third molars angulation, relative to the occlusal plane and adjacent second molars, were obtained by subtracting post- treatment from pre- treatment values. Statistically significant change in the angulation of both upper and lower third molars, relative to the occlusal plane and second molars, were found in the extraction group as compared to nonextraction group. The extraction of first premolars during orthodontic treatment significantly improved the angulation of third molars toward uprightening.